In Situ GWAS in Two Range‐Edge Populations of European Beech ( Fagus sylvatica L.) Identify Genetic Factors of Adaptation to Climate Change - Lauren Clément; Andrea Modica; Isabelle Lesur Kupin; Christophe Plomion; Catherine Bodénès; Grégoire Le Provost; Sylvie Oddou‐Muratorio; Katrin Heer; Marie Mirouze; Marie‐Christine Carpentier; Bartosz Ulaszewski; William Marande; et al. (Molecular Ecology, 2026)
In forest tree populations, the timing of budbreak (TBB) depends on several factors, both environmental and genetic. The genomic architecture underlying this trait is still not fully characterized. So far, common garden experiments have highlighted a few genomic regions with little heritability, while the whole spectrum of TBB variation observed in the wild still remains unexplored. We performed an in situ genome‐wide association study (GWAS) to investigate the genetic and environmental bases of phenotypic variation in budbreak in two wild range‐edge populations of the temperate continental tree, European beech ( Fagus sylvatica L.) surveyed in two consecutive years. We found distinct significant loci between populations and among years, suggesting that local adaptation has occurred and that genotype‐by‐environment interactions contribute to the observed variation. The phenotypic variance explained by the significant loci is between 0.2% and 54% for field data and 0% to 59% for modelled data, which suggests that while some traits are polygenic, some others are influenced by a few loci with large effects in the population, which demonstrates the relevance of conducting in situ GWAS in multiple populations. Our findings provide novel insights into the complex genetic architecture of TBB in forest trees. The genetic diversity of budbreak control provides opportunities for selection that could be used through assisted migration to help prepare beech forests to face climate change.